Wakalah Contract on Delivery Services: A Comparative Study - Wiam Milayanti; Indri Paramithasari (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
The purpose of this research was to determine the use of wakalah contracts on Citilink and Pos Indonesia delivery services and to determine the advantages and disadvantages of Citilink and Pos Indonesia delivery services. This research used a qualitative approach and combines secondary data, interviews, observations and documents. The results of this research indicated that the wakalah contracts that exist at Citilink and Pos Indonesia were the same but the comparison was in the service or when doing this wakalah contract Citilink cannot transact directly because Citilink is located in a city not in a village, while Pos Indonesia can serve and transact directly because Pos Indonesia already exists in every sub-district. Citilink's advantages included more punctuality, guaranteed service and security, solutions for geographical differences between regions. While Pos Indonesia, including PT Pos Indonesia, was more trusted than similar products that provided services such as those that can be provided by Pos Indonesia, wider area coverage, domestic shipping rates and uniform operating hours longer, excellent service. The disadvantage of Citilink was that it costs more. While Pos Indonesia, including PT Pos Indonesia, was still less well-known compared to other shipping services because of the views of the people of Pos Indonesia, it can only serve mail delivery services, delivery of destination packages in the village, the delivery system for goods was different between in Villages and Cities.